IMPLEMENTASI KEBIJAKAN SUBSIDI KENDARAAN LISTRIK MENURUT PERATURAN GUBERNUR DKI JAKARTA NOMOR 38 TAHUN 2023 DI KOTA JAKARTA - Sarah Bifitri Andrayani; Ari Subowo (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2026)
This study examines the implementation of the electric vehicle subsidy policy regulated under Article 1 of Jakarta Governor Regulation Number 38 of 2023, which provides tax exemptions for Battery Electric Vehicles (BEVs). Using a descriptive qualitative approach, this research analyzes how the policy is carried out and identifies the factors that hinder its effectiveness. The findings reveal that although the policy has been implemented according to regulations, its impact on improving air quality and increasing EV adoption remains limited. Key challenges include uneven communication, insufficient resources, suboptimal implementer commitment, and complex bureaucratic structures. The subsidy also tends to benefit higher-income groups, raising concerns about policy equity. Strengthening coordination, enhancing public outreach, and improving governance practices are necessary to optimize policy implementation.